Thực trạng quản lí hoạt động giáo dục ở một số trường phổ thông có nhiều cấp học trên địa bàn thành phố Hà Nội theo hướng tiếp cận giáo dục giá trị văn hoá - Trần, Quang Hưng (Tạp chí Giáo dục, 2025)
In the context of fundamental and comprehensive innovation of Vietnamese education, educational activities, including experiential activities at the primary level and experiential and career guidance activities at the secondary and high school levels, have become a mandatory part, playing an essential role in realizing the goals of the 2018 General Education Program. Effective management of these activities in the school education plan, from determining goals, content, and organization forms to implementation conditions, ensures education quality and contributes to the comprehensive development of students’ qualities and competences. In this article, the author focuses on assessing the awareness of managers and teachers about the importance, meaning, and goals of educational activities, as well as the current status of planning, organization, implementation, direction, inspection, control, and conditions to ensure. Through a survey of education management staff at the department, division, and multi-level general schools, the article provides insight into the current status of educational management. It proposes efficient solutions, contributing to the orientation to improve the quality of general education today.